The Inaccessible Road to Motherhood — The Tragic Consequence of not having Reproductive Policies for Israelis with Disabilities - Dorfman, Doron (Columbia Journal of Gender and Law, 2015)
The desire of an individual to become a parent can be very strong, especially in ‘child-centric’ societies, where the idea of having children and raising a family is highly valued. In those societies, the prominent pro-natal nature translates into policies and laws regulating reproduction. The Jewish-Israeli society is a prime example of such a society where the use of state-funded Assisted Reproduction Technologies (ART) is the highest in the world—eight times higher than the international average. However, the road to becoming a parent is not as smooth to all members of Israeli society. A recent case that went all the way to the Israeli Supreme Court proved how the current Israeli reproductive policies, particularly surrounding third-party reproduction methods i.e., adoption or surrogacy, are inaccessible to people with disabilities (among other minority groups) who share the same great desire to become parents. The Ora Mor Yosef case revolves around a Jewish-Israeli woman with muscular dystrophy who could not bear a child because of her impairment. Her dream of becoming a mother was so powerful that after exhausting all of her other options, she used a surrogate, sperm donation, and egg donation to bring a baby into the world. However, the lack of genetic-biological connection to the baby led the courts to decide not to recognize Ora as the mother, meaning that she never had the chance to even see the baby. This Paper will examine the exceptional case of Ora Mor Yosef in a broad context and from a “disability legal studies” perspective. It will compare Israeli socio-legal treatment of what I refer to as the right to become a parent with the United States legal system and will show how Israeli law makes it more difficult for women with disabilities to have children. It will continue with a discussion on the concept of disabled motherhood from a comparative Israeli-American perspective. This discussion will illuminate that there are still universal struggles and hardships for people with disabilities, specifically women, as they endeavor to become mothers and in raising their children. By using a Disability Legal Studies framework and a socio-legal analysis, this interdisciplinary paper will bring to the foreground issues and ramifications that were not found in the original reasoning of the Israeli courts’ rulings on the Ora Mor Yosef case, and will demonstrate the crucial role legal institutions play in the social construction of disability and its treatment by society. It is my hope that this paper will therefore help bring more attention to the issue of disabled parents and prevent tragic instances like the one standing in the heart of this paper from recurring.